RESTful web service usage for online exit-survey at syiah kuala university as data verification method - Sayed Muchallil; Yudha Nurdin; . Ahmadiar; . Melinda (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Many applications are developed and deployed in Syiah Kuala University main server. These applications and information system are built as tools to help the University’ daily activities. Most of these applications have its own database. As a result, data is inconsistent, and the worst is redundant data cannot be avoided. The idea behind of this research is to build one centralized data that can be used as baseline to other applications. Since the main data of Syiah Kuala University are located behind the proxy which is no internet direct access allowed to the data. The proposed method to answer this problem is touse web service as a gateway for data transfer. This technique keeps the database from direct external access but the data itself can be seen without knowing where the real data is. This method has been used for Online Exit-Survey to proof that the system can verify the students’ data. Some student cannot be identified because their data were empty, the other because the data in centralized database server were only prepared for undergraduate students, so that the post graduate and professional students cannot be verified. For undergraduate students this online exit-survey works fine without error on verification phase